أثر تدريس الكيمياء في ضوء برنامج سكامبر SCAMPER على التحصيل وتنمية مهارات التفكير العليا لدى طالبات الصف الثاني الثانوي بمدينة أبها - الشهري، ابتسام محمد عبدالرحمن; الغنام، محرز عبده يوسف (المركز القومي للبحوث غزة, 2017)
This research aims to identifying the impact of chemistry teaching methods – based on SCAMPER program – on secondary school’s second grade students’ achievement and higher-order thinking skills development. In order to achieve this objective, the research adopted an experimental methodology. Moreover, it designed a pre-post-test for the experimental group and control group. The researcher also developed an achievement test and a higher-order thinking skills test. The experiment was applied to a random sample of secondary school’s second grade students in a city of Abha in Asir Province. The members of the study sample – which consisted of (58) students – were divided into two groups: an experimental group with (28) students. The students of this group studied the science curriculum’s unit: "hydrocarbons" based on SCAMPER program. The other group – the control group – consisted of (30) students, who studied the same unit in the usual traditional way. Research instruments were applied to the two groups of the study sample before the experiment – specifically during the first semester of the academic year 1434 - 1435 AH. and, at the end of the experiment, the same research instruments were applied once more to the two groups as a post-test. Research results indicated that there are statistically significant differences at the level (0.00) between the mean of the scores of the experimental group’s students and the mean of the scores of the control group’s students in the post-test of achievement or higher-order thinking skills test in favor of the experimental group. In light of these results, a number of recommendations and suggestions were made.
هدف البحث الحالي إلى التعرف على أثر تدريس الكيمياء في ضوء برنامج سكامبر ((SCAMPER على التحصيل، وتنمية مهارات التفكير العليا لدي طالبات الصف الثاني الثانوي ولتحقيق هذا الهدف اعتمد البحث المنهج التجريبي، وتم فيه اختبار تصميم للمجموعتين التجريبية والضابطة ذات الاختبار القبلي – البعدي وقد أعدت الباحثة اختبارا تحصيليا، بالإضافة إلى اختبار مهارات التفكير العليا وطبقت التجربة علي عينة عشوائية من طالبات الصف الثاني الثانوي في إحدى مدارس مدينة أبها بمنطقة عسير، بلغ عددها (58) طالبة، تم تقسيمها إلي مجموعتين: أحداهما المجموعة التجريبية البالغ عددها (28) طالبة، درسن وحدة "الهيدروكربونات" في ضوء برنامج سكامبر، والأخرى المجموعة الضابطة والبالغ عددها (30) طالبة، درسن الوحدة ذاتها بالطريقة المعتادة وقد تم تطبيق أدوات البحث قبليا علي مجموعتي البحث، وذلك خلال الفصل الدراسي الأول من العام الدراسي 1434 – 1435 ه، وفي نهاية التجربة تم تطبيق أدوات البحث نفسها بعديا علي المجموعتين وقد أشارت نتائج البحث إلى وجود فروق دالة إحصائيا عند مستوي (0.05) بين متوسطي درجات طالبات المجموعتين التجريبية والضابطة في التطبيق البعدي للاختبار التحصيلي، حيث حصلت المجموعة التجريبية علي متوسط (43.89) في مقابل الضابطة التي حصلت علي متوسط (26.53)، وكذلك في اختبار مهارات التفكير العليا حصلت التجريبية علي متوسط (99.32)، مقابل (13.53) للضابطة، ويتضح أن الفارق في اختياري التحصيل ومهارات التفكير العليا لصالح المجموعة التجريبية. وفي ضوء هذه النتائج تم تقديم بعض التوصيات والمقترحات
Keywords: التحصيل الدراسي; تدريس الكيمياء; برنامج سكامبر; التعليم الثانوي; مدينة أبها (السعودية); مهارات التفكير العليا